EFEKTIVITAS EKSTRAK ETANOL KULIT BUAH PISANG KEPOK (Musa balbisiana) DALAM MENGOBATI LUKA BAKAR PADA KULIT PUNGGUNG TIKUS JANTAN (Rattus norvegicus) - Astuti, Risti Widia; suhada, adriyan; Rahmawati, Sri (Politeknik Medica Farma Husada Mataram, 2018)
Thing nededÂ is kapok bananaâs skin that has been macerated for healing skin tight on second level deep. The ultimate goal of this research is to know the exact percentage of exstract ethanol of kapok bananaâs skin (Musa balbisiana) in healing skin tight to the back side of male (Rattus norvegicus) by comparing negative control group and control group (10%, 25%, 50%, 75% and 100%). Method used centralistic data to know the result of control group in 7 days treatments. The type of this research is library experimental, where the researcher used one shot case study. Itâs mean the researcher doing intervence to a particular group. The result of itâs intervence areobserved on independent variable.Furthermore, the result getting of the research is from all control group (10%, 25%, 50%, 75% and 100%) having ability healing better than negative control group. From control group 10% skin tight 2 cm to be 1,7 cm, healing everage is 6, 43%. Control group 25%skin tight 2cm to be 1,6 cm the same case with control group 50% healing everage is 10,71% and 12, 14%. Control group 50% and 75% skin tight 2 cm to be 1,5 cm having healing 15, 71% and 17,14%. From all control group the most effective healing is extract ethanol to be 1,4 cm healing ability is 20, 71%.